تطبیقات الجیل الثانى للویب فى مجال التعلیم الالکترونى بجامعة تبوک : دراسة حالة - د. سامح زینهم عبد الجواد (المجلة الدولية لعلوم المكتبات والمعلومات)
By browsing the World Wide Web and taking you between different sites,you may notice that some sites provide you with access to their content only;other sites may give you the opportunity to participate, comment and add contentto the site, called the first type of site, which gives you access to content withoutparticipation. The first generation of the Web (Web1.0), which is often transmittedcontent from the owner of the site to visitors, in contrast, we find that the newgeneration of the Web, which is called (Web2.0) means sites that providedservices, tools and software applications on the network Allow visitors and usersshare in content creation. It has changed the role of the user from visitor toreader to partner and writer, where the trend has changed to make contentbuilding happen through the participation of users and visitors after it was doneby webmasters alone.With the advent of Web2.0 Tools, which gave users confidence, createdan interactive social environment and enabled access to other services and sites,education experts began to seek to employ these services to enhance and enrichthe learning process. Consequently, the concept of the second generation oftools E-learning e-Learning2.0, which depends on the services of the secondgeneration of the Web, and this is the purpose of this study to identify the extentof the application of these tools in the educational process at the University ofTabuk like international universities